Risk Factors at Time of Primary ACL Reconstruction that Contribute to Significant Chondral Surface Change at Time of Revision ACL Reconstruction: A Prospective Study from the MOON and MARS Cohorts. Issue 7 (18th July 2016) - Kaeding, Christopher C.; Group, Mars
Objectives: Articular cartilage health is an important issue following primary anterior cruciate ligament reconstruction (ACLR). It is not clear what risk factors at the time of primary reconstruction affect future articular cartilage health. The purpose of this study was to examine risk factors affecting chondral surface change in a cohort from the time of primary ACLR to revision ACLR. Methods: Subjects who had both primary and revision data contained in the MOON and MARS registries were included. Data included chondral surface status (grade and size) at time of primary and revision, meniscal status (no treatment/repair, ≤33% excision, >33% excision) at time of primary, time from primary to revision ACLR, and age, sex, BMI, Marx, KOOS, and IKDC at time of revision. Significant chondral surface change was defined as >25% deterioration between time of primary and revision in the femoral condyle, tibial plateau, patella, or trochlea. Logistic regression was used to test each variable's contribution to significant chondral surface change in the medial compartment, lateral compartment, and patellofemoral compartment. Results: 134 subjects met our inclusion criteria. 34/134 (25.4%) had significant lateral compartment chondral surface change, 32/134 (23.9%) had significant medial compartment chondral surface change, and 31/134 (23.1%) had significant patellofemoral chondral surface change. Median age at time of revision was 19.5 years [IQ range 17-25] and median time from primary to revision was 462.5 days [IQ range 292-1049]. KOOS and IKDC at revision were not associated with significant chondral surface change in any compartment. Patients with >33% of their lateral meniscus excised had 13.5 times the odds of having significant lateral compartment surface change compared to subjects who either did not have lateral meniscal damage, had it repaired, or had an excision of ≤33% controlling for age (p<0.001). Patients with ≤33% excision of their medial meniscus had 4.5 times the odds of significant medial compartment surface change compared to subjects who either did not have medial meniscal damage, had it repaired, or had an excision >33% controlling for age (p=0.02). Patients had 9% increased odds of significant patellofemoral compartment surface change for each increased point on the BMI scale controlling for age (p=0.05). Odds of significant chondral surface change increased by 5% for each increased year of age (p ≤0.02) in all compartments. Median time from primary to revision surgery, age, and Marx are summarized by chondral change and meniscal status in Table 1. Conclusion: At the time of primary ACLR, excision of >33% of the lateral meniscus significantly increases the risk of worsening articular cartilage health in the lateral compartment at the time of revision ACLR. In the medial compartment, worsening articular cartilage health is significantly increased by excision of ≤33% of the medial meniscus. There appears to be an interaction between time, age, and activity in this cohort. Increased age is a risk factor for deterioration of articular cartilage in all compartments and increased BMI is a risk factor for deterioration of patellofemoral articular cartilage. Clinical Relevance: This is powerful evidence that the largest risk factor for subsequent tibial-femoral chondral degeneration after ACLR is meniscus status, especially for the lateral compartment. Maintaining or restoring meniscus integrity is integral to maintaining long term joint health after ACLR.